Experimental Investigation of the Properties of Glass and Steel Fiber Reinforced Cement Mortar - Nada Hamad Khalaf; Yasir Khalil Ibrahim1; Sahib Mohammed Mahdi (Genius Journals, 2022)
Plain mortar possess very low tensile strength, limited ductility and little resistance to cracking. Internal micro cracks are inherently present in mortar and its poor tensile strength is due to propagation of such micro cracks. Fibers when added in certainpercentage in the mortar improve the strain properties well as crack resistance, ductility, as flexure strength and toughness. In this study crimped steel fibers and glass fibers with length 30 mm were added with three volume fraction (0.25%, 0.5% and 0.75 %.) to improve characteristics of cement mortar. The total samples were casted into cube molds for compressive strength test and prism molds for flexural strength test. The density was studied as physical properties. Total numbers of samples were cured for3,14 and 28 days in water curing tank before test .The results have shown that the improvement in the properties of mortar, was observed with the increase of the volume fraction of fibers . The fiber type was found to be a key factor affecting the mechanicalperformance of the material.
Keywords: Cement mortar, glass fiber, steel fiber, compressive strength, flexural strength, volume fraction.